Aplikasi Prediksi Prestasi pada Siswa Menggunakan Algoritma C4.5 - Rahmat Musfikar; Henita Apriadinata; Bustami Yusuf (Jurnal Manajemen Informatika JAMIKA, 2023)
The development of computer technology that is increasingly modern, fast and practical greatly affects the lives of the wider community. With the existence of increasingly sophisticated technology, a country's education can foster people's abilities, form personalities and progress a dignified country in the context of educating the country's life. Therefore, education is becoming an increasingly large impact that encourages students to achieve the best achievements. One of the factors that support student achievement is craft, adequate facilities, academic grades and also quality educators. The purpose of this study is to determine the achievement of students by predicting using the C4.5 algorithm on the designed web-based application. This research uses the RAD (Rapid Application Development) method in the process of designing student achievement prediction applications using the C4.5 algorithm. The results of the designed application aim to make it easier for students to increase their potential. The application designed has become an alternative problem solving for student problems regarding achievements, both academic and non-academic. So that when students know it, they can easily continue to hone their respective interests and talents.